Perencanaan Penggunaan Lahan Untuk Pengembangan Budidaya Tembakau di Kabupaten Temanggung - Rahadian Adi Prasetyo; Ronny Mulyawan (Berkala Ilmiah Pertanian, 2023)
Tobacco is one of the importan commodities in Temanggung Regency. Temanggung’s tobacco has a nicotine content from 3 – 8%, so it is used as one of the main flavoring ingredients in manufacture of cole cigarettes. The rapid development of tobacco cultivation land in Temanggung Regency was not followed by site selection according to land capability class and land suitability. The aim of this study were to, 1) calculate the aviability of land for the development of tobacco cultivation, 2) determine the land suitability class for tobacco cultivation. The matching method is use in land suitability class. Extensification of tobacco cultivation land in temanggung regency can be carrie out on land with suitability class S3 (according to marginal) covering an area of 17.490,90 ha, covering a dry area of 11.975 ha; rainfed rice fields 3.622,9 ha; and shurbs 1.893 ha . Actual land suitability class of land aviable, among others S3na (8.293,98 ha), S3nr,na (3.621,96 ha), S3rc,na (2.389,78 ha), S3tc,nr,na (1.014,93 ha), S3tc,na (787,04 ha), S3tc (402,73 ha), S3tc,nr (343,43 ha), and S3tc,rc (1,17 ha). Potential land suitability class of land aviable, among others S2na (8.293,98 ha), S2nr,na (3.621,96 ha), S3tc (2.548,13 ha), S3rc (2.389,78 ha), and S3tc,rc (1.17 ha).